THE GENERATION Z PHENOMENON AND ITS IMPLICATIONS IN THE WORKFORCE - Lina Dameria Siregar; Wita Farla WK; Siti Herlinda (SEAN Institute, 2023)
Organizations around the world are currently facing a business environment that is experiencing VUCA (volatile, uncertain, complex and ambiguous). The proportion of Generation Z is the proportion of the